До ідеологічних основ української нації і української мови - Ткаченко, О.Б. (Мовознавство, 2010)
Статтю присвячено ідеологічним основам української нації і української мови, які утворюються різними проявами української національної релігії, тобто національної традиції, утіленої в історії та культурі України. У зв’язку з цим розглядаються конкретні ідеологічні проблеми, важливі для подальшого існування України як держави. The article is devoted to the ideological foundations of the Ukrainian nation and the Ukrainian language which are formed by different manifestations of the Ukrainian national religion, that is of the national tradition incorporated in the history and the culture of Ukraine. There are considered concrete ideological problems, important for the subsequent existence and the development of Ukraine as a State.